Development of in-house rose bengal plate test for diagnosis of brucellosis in cattle and goats - Mohammed Sani, Yahaya (2016)
Brucellosis is endemic in South East Asia. Cattle and goats are considered as main livestock in Malaysia due to increase local demand for their milk and meat. This study was designed to develop an in-house Rose Bengal plate test (LRBPT), using local B. melitensis isolate and to determine the analytical and diagnostic performance characteristics of the LRBPT, using serum samples from goats and cattle respectively. The performance of LRBPT was compared to commercial RBPT produced by commercial producers. Comparison was performed using compliment fixation test (CFT) as the gold standard. The isolates were reconfirmed using colony morphology, biochemical test and PCR amplification of 16S RNA. All isolates were identified as B. melitensis and revealed a similar pattern to the reference strain 16M. Therefore one isolate was chosen as antigen for development of LRBPT. The sensitivity and specificity was calculated using CFT as the gold standard. Out of 1063 goat sera analysed 364(34.24%), 335(31.51%), and 373(35.08%) were positive by LRBPT, commercial RBPT-B. melitensis (cRBPT-B.melitensis), and CFT respectively. The sensitivity calculated for the LRBPT compared with CFT was 90.1% while cRBPT-B. melitensis was 85.0%. However, the specificity of the LRBPT was lower (95.9%), than the cRBPT-B. melitensis (97.4%). Similarly, the positive predictive value (PPV) and negative predictive value (NPV) of the LRBPT are 92.3%, and 94.7%, respectively, compared to that of cRBPT-B.melitensis which is 94.6%, and 92.3% respectively. Furthermore, it was observed that the LRBPT has a better value of NPV (94.7%) than that of the cRBPT- B. melitensis NPV (92.3%). However the cRBPT- B. melitensis has a higher value of PPV (94.6%), than LRBPT (92.7%). The performance of the LRBPT was also investigated using serum samples collected from cattle. The sensitivity and specificity was calculated using cRBPT-B. abortus as the reference or gold standard. The study found that out of 1000 cattle sera analysed 304(30.4%), 282(28.2%), and 208(20.8%) were positive by LRBPT, cRBPT- B. melitensis and cRBPT-B.abortus respectively. Nevertheless the LRBPT (88.9%) is still more sensitive compared to cRBPT-B. melitensis (84.1%). While the cRBPT-B. melitensis has higher specificity (86.5%), than LRBPT (85.0%). Furthermore, it was also observed that the PPV of the LRBPT is lower (60.9%) when compared to that of cRBPT-B. melitensis (62.1%). Similarly the NPV of the LRBPT is also higher (96.7%) than that of cRBPT-B. melitensis (95.4%). High sensitivity and low cost LRBPT compared to cRBPT-B. melitensis test kit was successfully developed. It was here by recommended that this diagnostic test was suggested to replace the available cRBPT-B. melitensis which is relatively more expensive and less sensitive in detection of brucellosis in cattle and goats. It could also be used for epidemiological surveillance of goat and cattle brucellosis in Malaysia.